2008
DOI: 10.1080/00365520801908928
|View full text |Cite
|
Sign up to set email alerts
|

Non-erosive and erosive gastroesophageal reflux diseases: No difference with regard to reflux pattern and motility abnormalities

Abstract: No difference was found between NERD and mild to moderate ERD in terms of acid exposure time and esophageal motor abnormalities. To a certain extent, ERD is a "more complicated" form of the disease. Host factors related to a particular patient (e.g. mucosal defense, genetics, acid clearance) might be responsible for the development of esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
3
15
4
1
Order By: Relevance
“…No difference was found between NERD and mild to moderate ERD in terms of acid exposure time and esophageal motor abnormalities [71]. Moreover, there was general agreement that there was no consistent evidence for abnormalities of gastric emptying, of salivary secretions or esophageal mucosal secretions in the pathogenesis of NERD.…”
Section: Pathobiological Mechanismsmentioning
confidence: 91%
See 1 more Smart Citation
“…No difference was found between NERD and mild to moderate ERD in terms of acid exposure time and esophageal motor abnormalities [71]. Moreover, there was general agreement that there was no consistent evidence for abnormalities of gastric emptying, of salivary secretions or esophageal mucosal secretions in the pathogenesis of NERD.…”
Section: Pathobiological Mechanismsmentioning
confidence: 91%
“…One recent study suggested that a small (<3 cm) hiatus hernia may contribute to the development of NERD, whereas an axial length of >3 cm was associated with a more severe disease [84], and in another study of patients with NERD and ERD hiatus hernia was found in 44 and 56%, respectively (not significantly different) [71]. …”
Section: Pathobiological Mechanismsmentioning
confidence: 99%
“…A tendency for NERD+ patients to have a higher mean LES pressure than ERD patients has also been reported in other studies, although the difference failed to reach statistical significance [14,20] . Findings for esophageal body motility did not differ significantly between patients with NERD+ and those with ERD, apart from a slight tendency for the distal wave amplitude to be greater in the first group.…”
Section: Physiopathological Patternmentioning
confidence: 68%
“…Hiatal hernia is currently assumed to be one of the physiopathological factors contributing to the onset of GERD by reducing LES competence and interfering with esophageal clearance [17,18] . Hiatal hernia is apparently a dominant predictor of erosive esophagitis [19] but it has been little studied in patients with NERD who are less likely to have hiatal hernias than patients with esophagitis [14,5,20] .…”
Section: General Considerations: Study Populationmentioning
confidence: 99%
“…Ghosh et al (2008) reported that weak mid esophageal contractions at the proximal smooth-muscle segment appear to be the cause of impaired clearance function. Martinek et al (2008) reported no difference between NERD and mild to moderate erosive esophagitis in terms of motor abnormalities. However, this study was performed using conventional monometry.…”
Section: Discussionmentioning
confidence: 99%